A parresia política como ação filosófica: um estudo do curso Le gouvernement de soi et des autres , de Michel Foucault - Silva, Afrânio Tenório da (2012)
The purpose of this work is the reading of the Le gouvernement de soi et des autres course, pronounced by Michel Foucault in 1983, on Collège de France. The aim is a reflexion on philosophy as a form of veridiction. The politics parrhesia is a form of philosophical veridiction that takes place in the meeting between philosophy and politics. This dissertation examines two built spaces on Antiquity for the politics parresia practice: the first one is the democratic city; the second one is the Prince s soul. Passing through the tragedy analysis of Ion, from Euripides, wherein parses the democratic parrhesia, and the VII Plato s Charter, wherein parses the autocratic parresia, it comes a question on how the parrhesia s concept, emerged from the early days of our culture, it means in Greek Antiquity, can echo on Modernity, trough the Aufklärung text from Kant. The result is a reflexion about the current philosophy and its contribution to a possible link between the own government and the others one